Prevalence of Antibodies to Simbu Serogroup Viruses in Cattle in Sudan - Mohammed O. Hussien; Shima H. Alfaki; Khalid A. Enan; Rana A. Gafar; Amira M. Elhassan; Khalid M. Taha; Abdel Rahim M. El Hussein (Veterinary Medicine International)
The Simbu serogroup is one of the serogroups that belong to the Orthobunyavirus genus of the family Peribunyaviridae. Simbu serogroup viruses are transmitted mainly by Culicoides biting midges. Meager information is available on Simbu serogroup virus infection in ruminants in Sudan. Therefore, in this study, serological surveillance of Simbu serogroup viruses in cattle in seven states in Sudan was conducted during the period from May, 2015, to March, 2016, to shed some light on the prevalence of this group of viruses in our country. Using a cross-sectional design, 184 cattle sera were collected and tested by a commercial SBV ELISA kit which enables the detection of antibodies against various Simbu serogroup viruses. The results showed an overall 86.4% prevalence of antibodies to Simbu serogroup viruses in cattle in Sudan. Univariate analysis showed a significant association (p=0.007) between ELISA seropositivity and states where samples were collected. This study suggests that Simbu serogroup virus infection is present in cattle in Sudan. Further epizootiological investigations on Simbu serogroup viruses infection and virus species involved are warranted.